Book review: Clancy, Joy. 2013: Biofuels and Rural Poverty. (April 2017) - Eswarappa, KASI
Clancy, Joy. 2013: Biofuels and Rural Poverty . London and New York: Routledge. 205 pp. 79.95 (Hardback). ISBN: 9781844077199.